2023
DOI: 10.1111/1471-0528.17395
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a universal late third‐trimester scan for fetal growth restriction on perinatal outcomes in term singleton births: A prospective cohort study

Abstract: Objective To investigate perinatal mortality, morbidity and obstetric intervention following the introduction of a universal late third‐trimester ultrasound scan for growth restriction. Design Prospective cohort study. Setting Oxfordshire (OUH), UK. Population Women with a non‐anomalous singleton pregnancy undergoing pregnancy care and term delivery at OUH with an estimated due date (EDD) of birth between 1 January 2014 and 30 September 2019. Methods Universal ultrasound for fetal growth restriction between 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…This was a secondary analysis of the population from the OxGRIP study, which has been described previously 10 . All women with a singleton pregnancy and an estimated due date between January 2014 and September 2019 were included.…”
Section: Methodsmentioning
confidence: 99%
“…This was a secondary analysis of the population from the OxGRIP study, which has been described previously 10 . All women with a singleton pregnancy and an estimated due date between January 2014 and September 2019 were included.…”
Section: Methodsmentioning
confidence: 99%
“…186 In a pragmatic screening study in nulliparous women, SGA was detected in 57% with routine third trimester USS compared with 20% with USS by clinical indication, but it is only when fetal growth velocity was combined with fetal biometry that a subset of SGA fetuses at risk of increased neonatal morbidity was identified. 187 Studies published since the NICE review have similarly demonstrated an unclear effect on perinatal mortality, 188,189 and a systematic review of diagnostic performance concluded that for a fixed 10% false positive rate sensitivity was higher for AC than EFW and better performance when the scan was carried out near term and to detect FGR rather than SGA. 190 The NICE committee did note that the evidence in their review was overall moderate to low quality and that within their recommendation not to offer routine third trimester USS there is an inherent assumption that risk assessment and selective scanning is being appropriately applied.…”
Section: [Evidence Level 2+]mentioning
confidence: 99%
“… 5 Ultrasound (US) estimations of fetal weight and maternal and fetal Doppler abnormalities most commonly inform the current clinical management of suspected FGR. 6 However, universal third-trimester US screening for FGR was found to be a poor predictor of perinatal morbidity and mortality 7 and the significant cost burden associated with US further limits the breadth of its application to the wider pregnancy population in both high- and low-resource healthcare settings. 8 As such, poor antenatal detection of FGR has been associated with a significant increase in stillbirths, adverse perinatal outcomes, and adult-onset complications.…”
Section: Introductionmentioning
confidence: 99%